Pendidikan Karakter Berbasis Kearifan Lokal Masyarakat Lampung pada Novel Negarabatin: Negeri di Balik Bukit : Negeri di Balik Bukit (2022) - Saniro, Roma Kyo Kae; Andina Meutia Hawa ,; Dyani Prades Pratiwi ,; Noni Sukmawati , (Jurnal Serambi Ilmu, 2024)
This research aims to describe the values of local wisdom in the novel Negarabatin: Negeri di Balik Bukit by Udo Z. Karzi (2022). The research method used is descriptive analysis with a literary anthropology approach elaborated with the presence of character education values. The result of the research indicating several values of local wisdom of the Lampung community in their perspective of life. These include the use of the name "Uyung" to bridge existing gaps as a form of tolerance and peace; the practice of reciting the Quran and the tradition of "bediom" followed by circumcision as religious values; and "ngusi" (clearing potential to serve as tools for character education, representing the Lampung community that can be passed on to the younger generation of Lampung and Indonesia more broadly. The implications of this research emphasize the importance of utilizing local literature as a source of values in developing character education, which can help shape positive character traits in children and adolescents within the context of their culture and society. Schools and educational institutions can consider integrating local literary materials into the curriculum to make it easier for students to access and understand these values. Furthermore, efforts are needed to document and promote local literary works as sources of inspiration in developing character education modules.